The Age of OrthoInfo: A Randomized Controlled Trial Evaluating Patient Comprehension of Informed Consent. (5th October 2016) - Egekeze, Nkemakolam; Dubin, Jonathan; Williams, Karen; Bernhardt, Mark
Abstract : Background: Integral to an orthopaedic surgeon-patient informed consent discussion is the assessment of patient comprehension of their medical care. However, little is known about how to optimize patient comprehension of an informed consent discussion. The purpose of our study was to evaluate three time-controlled informed consent discussion methods to determine which optimized patient comprehension immediately after the discussion. Methods: Sixty-seven consecutive patients with knee osteoarthritis who were considered medically appropriate for a knee corticosteroid injection were enrolled in our trial. Participants were randomized and were allocated into one of three groups in a parallel fashion and 1:1:1 ratio. Our three groups varied by sensory input and included verbal (hearing), verbal and video (hearing and sight), and verbal and model (hearing, sight, and touch). Each participant listened to a 10-minute scripted lecture given by a researcher; this lecture was based on content from the American Academy of Orthopaedic Surgeons patient education web site OrthoInfo. Patient comprehension was assessed after the lecture using a validated questionnaire called the Nkem test. Our primary outcome evaluated patient comprehension utilizing a pairwise comparison of mean comprehension scores between the groups. The primary outcome was analyzed using a one-way analysis of variance with the least significant difference calculated post hoc and a 95% confidence interval (95% CI). The health-care staff, study participants, and outcome assessor were each blinded to group assignments. Results: The mean comprehension scores were 84% (95% CI, 79% to 88%) for the verbal and model group, 74% (95% CI, 63% to 80%) for the verbal and video group, and 71% (95% CI, 61% to 80%) for the verbal group. The omnibus analysis of variance was significant and showed a difference among the groups (p = 0.019). The pairwise comparison of the groups using the least significant difference calculated post hoc showed that the verbal and model group outperformed the verbal group (p = 0.01) and the verbal and video group (p = 0.023). Conclusions: Multisensory patient education incorporating OrthoInfo and an anatomic model optimized patient comprehension immediately after a time-controlled informed consent discussion. This finding could play an important role in improving surgeon-patient communication in the field of orthopaedic surgery.